Diaspora theory and transnationalism - Lahiri, Himadri (Literary/cultural theory, 2019)
This book examines issues related to transnational movements of human beings and capital from the vantage point of contemporary perspectives, and literary and cultural tropes of such experiences. It discusses the nuanced differences between 'diaspora' and 'transnationalism', and traces the trajectory of theories of diaspora and transnationalism. It enumerates the history of old and new diasporas, explains how diaspora generates acculturation and cultural hybridity, and shows how it impacts ideologies of gender, sexuality, religion and state policies, and politics of immigration and citizenship. The volume also discusses how Diaspora Studies may reconfigure its priorities in the future.